LITERASI DIGITAL ETHIC GURU SEKOLAH DASAR - Kurniati Rezki Fitra; Seni Aprilliya; Dindin Abdul Muiz Lidinillah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
Digital ethics is currently very important in dealing with developments in the field of information and communication technology. Because in understanding digital literacy, it is not only knowing the extent to which technology is used as a learning resource, but how a person is wise in filtering the receipt of information that is easily obtained through digital technology. It is necessary to build digital literacy ethics for teachers to be a form of anticipation of the bad impacts that arise from the low understanding of digital literacy ethics, internet ethics (Nettiquette). This study aims to determine the digital literacy ethics of elementary school teachers. This research uses a quantitative approach research design with internet survey research methods. The findings of this study indicate that the basic knowledge of elementary school teachers on digital literacy ethics is in a very good category in the context of internet ethics, negative information and content in the digital space, interaction, participation, and collaboration with digital ethics and applicable regulations, as well as interacting. and conduct electronic transactions in accordance with applicable regulations, and teachers are expected to be able to apply digital literacy ethics in their daily lives.